Does preference rank predict substitution for the reinforcer for problem behavior? a behavioral economic analysis. Issue 2 (14th March 2018) - Frank‐Crawford, Michelle A.; Castillo, Mariana I.; DeLeon, Iser G.
Abstract : Predictions made under low response requirements inherent in most preference assessments (PAs) do not guarantee the utility of stimuli in treatments. We examined whether PA rank would predict how well stimuli supported compliance for children with escape‐maintained problem behavior by examining the relation between PA rank and demand elasticity across five fixed‐ratio values. Three patterns were observed: All stimuli were selected equally across values, higher ranked stimuli were selected more at higher values, and something other than the highest ranked stimulus was selected more at higher values (i.e., mixed correspondence).